5/6 - 3/8
Rewrite the fractions to have a common denominator:
5/6 x 4 = 20/24
3/8 x 3 = 9/24
Now you have 20/24 - 9/24 = 11/24
The answer is D. 11/24
Answer:
$316.46
Step-by-step explanation:
total cost = 109.5% = 109.5% x $289 = $316.46 (2dp)
Topic: Percentages
If you like to venture further, please give my Instagram page a follow (learntionary). I'll be constantly posting math tips and notes! Thanks!
Answer:
a. 15 on top 8 on bottom
b. 2 on top -3 on bottom
c. 4 and 2
d. 4 on top 8.5 on bottom
e. -3 and -4
Step-by-step explanation:
multiply the two numbers on the sides to get the top answer and add them together to get the bottom answer.
Answer:
Hope this helps sorry I'm in class right now
Step-by-step explanation:
This is not a polynomial equation unless one of those is squared. As it stands x=-.833. If you can tell me which is squared I can help solve the polynomial.
Ok, that is usually notated as x^3 to be clear. I'll solve it now.
x^3-13x-12=0
Then use factor theorum to solve x^3-13x-12/x+1 =0
So you get one solution of x+1=0
x=-1
Then you have x^2-x-12 now you complete the square.
Take half of the x-term coefficient and square it. Add this value to both sides. In this example we have:
The x-term coefficient = −1
The half of the x-term coefficient = −1/2
After squaring we have (−1/2)2=1/4
When we add 1/4 to both sides we have:
x2−x+1/4=12+1/4
STEP 3: Simplify right side
x2−x+1/4=49/4
STEP 4: Write the perfect square on the left.
<span>(x−1/2)2=<span>49/4
</span></span>
STEP 5: Take the square root of both sides.
x−1/2=±√49/4
STEP 6: Solve for x.
<span>x=1/2±</span>√49/4
that is,
<span>x1=−3</span>
<span>x2=4</span>
<span>and the one from before </span>
<span>x=-1</span>